The role of accounting in the German financial system - Christian Leuz; Jens Wüstemann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This chapter analyzes the role of financial accounting in the German financial system. It starts from the common perception that German accounting is rather 'uninformative'. This characterization is appropriate from the perspective of an arm's length or outside investor and when confined to the financial statements per se. But it is no longer accurate when a broader perspective is adopted. The German accounting system exhibits several arrangements that privately communicate information to insiders, notably the supervisory board. Due to these features, the key financing and contracting parties seem reasonably well informed. The same cannot be said about outside investors relying primarily on public disclosure. A descriptive analysis of the main elements of the Germany system and a survey of extant empirical accounting research generally support these arguments.
urn:nbn:de:hebis:30-10219
Keywords: M41; G3; D82; K0; 330; Accounting; Disclosure; Germany; Standards; Survey